Deteksi Molekuler Asosiasi Begomovirus dengan Penyakit Keriting Kuning Cabai di Pakis dan Banyuurip, Magelang Indonesia - Effi Alfiani Sidik (JURNAL VIGOR, 2021)
Begomovirus associated to yellow-curl disease, is an obstacle to the production of chilli in various countries, especially in Indonesia. The characterization of the visual symptoms caused by Begomovirus varies widely. The detection method used must be effective and accurate therefore provide a precise control. This study aims to detect Begomovirus infection using PCR and identify symptoms of yellow-curl disease in Magelang Regency. The research included a sample collection on chilli in Pakis and Banyuurip (Magelang), observing of variation of symptoms of Begomovirus infection, and molecular detection. Primer pairs pAL1v1978/pAR1c715 has successfully detected the association of Begomovirus with yellow-curl disease on chilli at Pakis by symptoms: mosaic, leaf cupping, plant stunting, curling, and malformation. PCR results showed that Begomovirus was not association with yellow-curl disease on chilli at Banyuurip. Molecular evidence for Begomovirus is absolutely necessary because detection based on the visual appearance of symptoms alone is not sufficient to prove infection.